MODEL FOR DEVELOPING THE COGNITIVE ACTIVITY OF FUTURE TEACHERS IN THE CONTEXT OF INNOVATIVE EDUCATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines a model for developing the cognitive activity of future teachers in the context of innovative education. The study analyzes modern pedagogical technologies, interactive teaching methods, and the potential of the digital learning environment in enhancing students’ cognitive engagement. The structural components, implementation stages, and effectiveness criteria of the proposed model are substantiated, focusing on fostering independent thinking, analytical skills, and reflective competencies in prospective teachers.